Effect of HM substrates' cutting edge roundness manufactured by laser machining and micro-blasting on the coated tools' cutting performance. (August 2017) - Bouzakis, K.-D.; Charalampous, P.; Kotsanis, T.; Skordaris, G.; Bouzakis, E.; Denkena, B.; Breidenstein, B.; Aurich, J.C.; Zimmermann, M.; Herrmann, T.; M'saoubi, R.
Highlights: Cemented carbide inserts were laser-machined for shaping their cutting radii. Diverse laser machining data led to variously thick thermal affected zones (TAZ). The developed TAZs micro-structures and mechanical properties were investigated. The coated tools cutting performance were tested in milling Inconel 718 and TiAl4V6. Adequate laser machining parameters and treatments increase the coated tool life. Abstract: The effective application of laser machining for manufacturing the cutting edge roundness of cemented carbide inserts was investigated in a cooperative work of the Scientific Technical Committee (STC) "Cutting" of the International Academy for Production Engineering (CIRP). Machining with diverse laser beam pulsing duration and feed velocity as well as micro blasting were employed prior to the coating deposition for shaping the cutting tool's edges. The wear behaviour of the coated inserts was tested in milling TiAl6V4 and Inconel 718. Considering the inserts' surface micro-structure and mechanical properties developed after the laser treatment, the coated tools' cutting performance deterioration or improvement compared to untreated substrates was explained.